MENCERMATI EKSISTENSI DAN PERANAN AGAMA-AGAMA DALAM MEMBANGUN NEGARA KESATUAN REPUBLIK INDONESIA (Sebuah Tinjauan Filosofis-Sosial Politik-Moral Etik) - Lintong, Marthinus Marcel (Fides et Ratio : Jurnal Teologi Kontekstual Seminari Tinggi St. Fransiskus Xaverius Ambon, 2017)
The main focus of this simple papers was intended to briefly describe the nature of the role and exsistence of religions in developing the Integrated State of the Republic of Indonesia through these three perspectives: 1) philosophy (nature or essence of religion in the context of philosophy), 2). Socio-politics (role of religion in the context of social life and its influence to legacy of the public policy. 3). Ethics and morality (role of religion in grounding and constructing the values of Indonesian’s nation-state). The last section of this papers would be the conclusion about the actualization of religious life in Indonesia by which we used the terms of being religion as a ‘gift or blessing for all mankind’.